Improving Resilience in Water Distribution System - Ismail, Ahmed Farid (2022)
A Master of Science thesis in Construction Management by Ahmed Farid Ismail entitled, “Improving Resilience in Water Distribution System”, submitted in December 2022. Thesis advisor is Dr. Md. Maruf Mortula. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).